STRATEGI GURU AKHLAK TASAWUF DALAM MENINGKATKAN SELF CONTROL SISWA KELAS XI MAN PK MAN 1 YOGYAKARTA - Antin Rista Yuliani; Indal Abror; Eva Latipah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the strategies of Sufism Akhlak teachers in improving the self-control of class XI MAN PK MAN 1 Yogyakarta students. This research uses a qualitative descriptive research type. Data collection techniques: observation, interviews, documentation, and questionnaires. Data analysis: data reduction, data presentation, and drawing conclusions. The results of this research are 1) The self-control of class XI MAN PK students is that out of 24 students, 5 students have good self-control and 19 students have poor self-control. The behavior under control of students is being late for class, being lazy, lying, making fun of friends, forgetting to do assignments, being late in submitting assignments, cheating on exams, cheating on friends' assignments, leaving the dormitory without permission, smoking, skipping lessons in the dormitory, and not collecting cellphones when in dorm. 2) The Sufism Akhlak teacher's strategy in increasing students' self-control is using modified discussion learning strategies, giving rewards and punishments, helping to solve students' problems, applying the concepts of learning from experience, habituation, example, giving advice, warnings and warnings. 3) The results achieved by the Sufism Akhlak teacher in increasing students' self-control are that the majority of students have shown good behavior. 4) Supporting factors are the example of Sufism Morals teachers, a good madrasa governance system, and Sufism Morals teachers' learning strategies. The inhibiting factors are peers and less strict punishment.